Precise in vivo adaptive optics imaging of retinal vessels - Oleg Zadorozhnyy; Andrii Korol; Illia Nasinnyk; Taras Kustrin; Volodymyr Naumenko; Nataliya Pasechnikova (Ukrainian Society of Ophthalmologists, 2023)
Adaptive optics (AO) provides new, unique opportunities for in vivo visualization of retinal vasculature. AO retinal vessel imaging can be utilized as a component of multimodal imaging tools to complement conventional diagnostic imaging modalities. Non-invasive and highly promising AO imaging of fundus structures allows the qualitative and quantitative assessment of early signs of retinal vascular remodeling associated with age, arterial hypertension, diabetes mellitus and other disorders.